CXCR5 and TIM-3 expressions define distinct exhausted T cell subsets in experimental cutaneous infection with Leishmania mexicana - Diupotex, Mariana; Zamora-Chimal, Jaime; Gajón, Julián A.; Bonifaz, Laura C.; Becker, Ingeborg (Frontiers in Immunology, 2023)
T-cell exhaustion is a key stage in chronic infections since it limits immunopathology, but also hinders the elimination of pathogens. Exhausted T (Tex) cells encompass dynamic subsets, including progenitor cells that sustain long-term immunity through their memory/stem like properties, and terminally-differentiated cells, resembling the so-called Tex cells. The presence of Tex cells in chronic leishmaniasis has been reported in humans and murine models, yet their heterogeneity remains unexplored. Using flow cytometry, we identified Tex cells subtypes based on PD-1, CXCR5 and TIM-3 expressions in draining lymph nodes (dLNs) and lesion sites of C57BL/6 mice infected with L. mexicana at 30-, 60- and 90-days post-infection. We showed that infected mice developed a chronic infection characterized by non-healing lesions with a high parasite load and impaired Th1/Th2 cytokine production. Throughout the infection, PD-1+ cells were observed in dLNs, in addition to an enhanced expression of PD-1 in both CD4+ and CD8+ T lymphocytes. We demonstrated that CD4+ and CD8+ T cells were subdivided into PD-1+CXCR5+TIM-3- (CXCR5+), PD-1+CXCR5+TIM-3+ (CXCR5+TIM-3+), and PD-1+CXCR5-TIM-3+ (TIM-3+) subsets. CXCR5+ Tex cells were detected in dLNs during the whole course of the infection, whereas TIM-3+ cells were predominantly localized in the infection sites at day 90. CXCR5+TIM-3+ cells only increased at 30 and 60 days of infection in dLNs, whereas no increase was observed in the lesions. Phenotypic analysis revealed that CXCR5+ cells expressed significantly higher levels of CCR7 and lower levels of CX3CR1, PD-1, TIM-3, and CD39 compared to the TIM-3+ subset. CXCR5+TIM-3+ cells expressed the highest levels of all exhaustion-associated markers and of CX3CR1. In agreement with a less exhausted phenotype, the frequency of proliferating Ki-67 and IFN- expressing cells was significantly higher in the CXCR5+ subset within both CD4+ and CD8+ T cells compared to their respective TIM-3+ subsets, whereas CD8+CXCR5+TIM-3+ and CD8+TIM-3+ subsets showed an enhanced frequency of degranulating CD107a+ cells. In summary, we identified a novel, less-differentiated CXCR5+ Tex subset in experimental cutaneous leishmaniasis caused by L. mexicana. Targeting these cells through immune checkpoint inhibitors such as anti-PD-1 or anti PD-L1 might improve the current treatment for patients with the chronic forms of leishmaniasis.